Textile electrodes for bioimpedance measuring - Judith Tabea Meding; Khorolsuren Tuvshinbayar; Christoph Döpke; Ferdinand Tamoue (Communications in Development and Assembling of Textile Products)
This article deals with the development and comparison of eight different electrodes made out of a cotton fabric substrate, a silver coated yarn and partly conductive finishes, i.e. a PEDOT:PSS Orgacon ICP 1050 dip-coating and a Powersil coating. The purpose is the application especially in the medical field of angiopathy like for bioimpedance measurements during compression therapies. To be able to compare the suitability of the electrodes, various tests have been performed of the coating abrasion resistance, the stability of electrical resistance values, as well as resistance and bioimpedance measurements. Significant differences between the electrodes regarding their resilience and resistance that are visualized in a value-added analysis were found, with one hand-embroidered, one machine-sewn and one commercial electrode showing optimum properties.